Nutritional adequacy of menus offered to children of 2 - 5 years in registered childcare facilities in Inanda, KwaZulu-Natal Province, South Africa - PF Nzama; Carin Napier (South African Medical Association, 2017)
Background. The number of children that spend a large part of the day at child care facilities has risen worldwide. The parent relies on care givers in child care facilities (CCFs) to provide children with balanced meals. Studies in various parts of South Africa that analysed CCFs menus have found that the menus do not satisfy the daily requirements of energy and micronutrients for children. With increased numbers of children attending CCFs and increased obesity prevalence in children in SA and in KwaZulu Natal information with regards to food presented at the facilities was of interest not only to compare the energy and micronutrient intake but to also to consider the dietary diversity offered to the children on a daily basis. Objective. The objective of this study was to analyse menus offered to children in CCFs in Inanda, KwaZulu-Natal for nutritional adequacy and to calculate the contribution the meals make to the Dietary Reference Intakes for children in the two to five year age category. Methods. Permission from the Department of Social Development in Durban (DSD) was obtained to approach the CCFs to participate in the study. Ten CCFs in the Inanda area were randomly selected from the DSD list of 45 registered CCFs. The researcher gathered menus, recipes and serving sizes from each of the 10 CCFs. Food Finder Version 3 Software (Medical Research Council SA), adjusted to include fortified wheat and bread products, was used to analyse the recipes. Results. The CCFs in Inanda served breakfast and lunch to the children on a daily basis. The top 20 list of foods offered cereal-based staples of rice and maize meal more frequently than meat, dairy products and fruit and vegetables. All the CCFs did not meet 60 percent of daily requirements for energy, fibre and calcium for children in this age group. Conclusion. Menus offered to children of age two to five years in registered CCFs in Inanda are nutritionally inadequate.